Thiazide Diuretics and Their Importance in Cardiac Diseases - Ismoilov Farrukh Dilshodovich; Zokirova Feruza Zokirovna; Malikova Marjona Alisher kizi; Rahmonov Khamza Abdukodirovich (Genius Journals, 2025)
Thiazide diuretics are widely used agents in the managing cardiovascular diseases, especially hypertension and chronic heart failure. They act by inhibiting sodium-chloride symporters in the distal convoluted tubule, leading to effective blood pressure reduction. This article explores their mechanism of action, clinical applications, and comparative benefits. A separate section highlights the etiology and classification of heart failure to provide clinical context. The pharmacodynamics and pharmacokinetics of individual thiazides—hydrochlorothiazide, chlorthalidone, indapamide, and metolazone—are discussed in detail. Evidence-based protocols and case studies further demonstrate their clinical value.
Keywords: Thiazide diuretics; heart failure; hypertension